Answer:
The equation of the tangent plane to the surface is given by
![6x+10y+z=-3](https://img.qammunity.org/2020/formulas/mathematics/college/n9ouneg3lsw6rh9v08j4g1elr6x6qc1ef4.png)
Explanation:
We can find the normal of the surface using the gradient over f(x,y,z), where the function is
![f(x,y,z)=-3x^2+x+5y^2-z=0](https://img.qammunity.org/2020/formulas/mathematics/college/10rmunxsaqesj7syc1xhz3o917knmdyo10.png)
And the gradient is
![\\abla f(x,y,z) =<-3x+1, 10y, -1>](https://img.qammunity.org/2020/formulas/mathematics/college/f71m485h5z85ep40sei5j0xswrvqfqvwfk.png)
Then the normal at the point (2,-1, -5) is
![\vec n =\\abla f(2,-1,-5)\\\vec n = <-3(2), 10(-1), -1>\\\vec n = <-6,-10,-1>](https://img.qammunity.org/2020/formulas/mathematics/college/votmqaolau9b6uonysvn1l4emplmrppn4n.png)
Then the equation of the tangent plane to the surface is given by
![\vec n \cdot (P-P_0)=\vec0](https://img.qammunity.org/2020/formulas/mathematics/college/vpzxk1z916wagi106t17a2walaookmvo20.png)
Replacing the given point and the normal we get
![<-6,-10,-1>\cdot <x-2, y+1, z+5>=0\\-6(x-2)-10(y+1)-(z+5)=0](https://img.qammunity.org/2020/formulas/mathematics/college/193dnty7ijalz2xd11c2u589j8ix4z54fv.png)
We can simplify a bit to get into standard form
![-6x+12-10y-10-z-5=0\\-6x-10y-z-3=0\\-6x-10y-z=3\\\\6x+10y+z=-3](https://img.qammunity.org/2020/formulas/mathematics/college/5rrwty5zlrvprwlkynslmk79cga4w66loz.png)